Екологічні показники при геолого-економчній оцінці родовищ корисних копалин на окремих стадіях геологічного вивчення та освоєння надр - Курило, М.М. (Екологічна безпека та природокористування, 2009)
Ecological indices systematization of geological-economical evaluation is realized. Peculiar properties of separate stages of exploration work are taken into consideration. While prospecting work general ecological factors are defined; during exploration work and projection ecological indices are realized in economical (mining cost, total investments volume); during exploitation works material losses concerned with ecological risks are assessed.